Pavlov’s Methodological Behaviorism as a Pre-Socratic Contribution of the Melding of the Differential and Experimental Psychology - Furedy, John J. (The Spanish Journal of Psychology, 2003)
The differential/experimental distinction that Cronbach specified is important because any adequate account of psychological phenomena requires the recognition of the validity of both approaches, and a meaningful melding of the two. This paper suggests that Pavlov’s work in psychology, based on earlier traditions of inquiry that can be traced back to the pre-Socratics, provides a potential way of achieving this melding, although such features as systematic rather than anecdotal methods of observation need to be added. Pavlov’s methodological behaviorist approach is contrasted with metaphysical behaviorism (as exemplified explicitly in Watson and Skinner, and implicitly in the computer-metaphorical, informationprocessing explanations employed by current “cognitive” psychology). A common feature of the metaphysical approach is that individual-differences variables like sex are essentially ignored, or relegated to ideological categories such as the treatment of sex as merely a “social construction.” Examples of research both before and after the “cognitive revolution” are presented where experimental and differential methods are melded, and individual differences are treated as phenomena worthy of investigation rather than as nuisance factors that merely add to experimental error.